The American occupation of Oriental Negros as revealed in the pages of Siliman truth (1903-1920) - Cleope, Earl Jude Paul L. (2006)
This paper is an attempt to depict the American occupation in Negros by looking through the pages of Siliman Truth, the first and sole periodical circulating in Negros Oriental during the early American period. Although Silliman Truth was a campus publication of Silliman Institute (founded 1901), it also served as the community paper when it came off the press in 1903. This trilingual (English, Cebuano, and Spanish) periodical was circulated until 1920 and its pages offer a vivid description of the early American period in Negros. At a glace, the periodical that was established by the American missionaries could be viewed as a tool that played a vital role in the American colonization process. Nevertheless, a thorough reading of the pages of the periodical would also showcase the legacy and hard work of the early American missionaries and civil servants who came to Negros. In addition, the ample information and descriptions give in the periodical text yield data on the historical development of Negros during the early yeas of the American period. Consequently, it is the modest aim of this paper to present the American period in Negros Oriental in a different way by looking into the pages of Silliman Truth. With this perspective, the paper will attempt to look into how the American occupation made an impact on the political, social, economic, educational, and cultural life of the Negrenses.